2013
DOI: 10.1002/app.39469
|View full text |Cite
|
Sign up to set email alerts
|

Non‐isothermal crystallization kinetics and morphology of mica particles filled biodegradable poly(butylene succinate)

Abstract: Biodegradable poly(butylene succinate) (PBS)/mica composites were prepared by melt blending. The non-isothermal crystallization kinetics, spherulitic morphology, and crystalline structure were investigated by DSC, POM, and WAXD, respectively. The concepts of ''crystallization rate coefficient'' and ''crystallization rate parameter'' were employed. The non-isothermal crystallization behavior was successfully analyzed by Avrami and Liu methods while the Ozawa method failed to describe it. The WAXD and POM result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This leads to an overall increase in the crystallization rate. The t 1/2 values for mica/PBSu composites were less than those for neat PBSu at a fixed cooling rate, according to Zhang et al [ 35 ], indicating that the presence of mica particles speeds up the non-isothermal crystallization process. Yacini et al [ 36 ] found a similar decreasing phenomenon during the non-isothermal process of the PBSu/multi-walled carbon nanotube composites.…”
Section: Resultsmentioning
confidence: 86%
“…This leads to an overall increase in the crystallization rate. The t 1/2 values for mica/PBSu composites were less than those for neat PBSu at a fixed cooling rate, according to Zhang et al [ 35 ], indicating that the presence of mica particles speeds up the non-isothermal crystallization process. Yacini et al [ 36 ] found a similar decreasing phenomenon during the non-isothermal process of the PBSu/multi-walled carbon nanotube composites.…”
Section: Resultsmentioning
confidence: 86%
“…Commonly, an increasing content of a plasticizer leads to a decrease in the viscosity of the rubber mixture, and therefore, its processability will be improved [9]. In the rubber industry, paraffinic and aromatic oils have been very important additives that can reduce viscosity, increase the processability, enhance the elastomeric performance, result in better filler dispersion, lower the glass temperature transition, and result in low hardness and temperature resistance [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…12, 13 Unfortunately, it still lacks the mechanical and thermal properties needed for industrial application. 14-19 It is necessary to modify PBS to improve the properties for diverse applications. 2, 20, 21…”
Section: Introductionmentioning
confidence: 99%